PENGARUH PELAYANAN, PRODUKTIVITAS, KOMPENSASI, DAN SUMBER DAYA MANUSIA TERHADAP KINERJA PDAM TIRTA KAMPAR – KOTA BANGKINANG - Suryati Nur’aini; Amir Hasan; Al Azhar A ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the impact of the service, productivity, compensation and human resources to the performance of PDAM Tirta Kampar - City Bangkinang with multiple regression method. The aim of this study was PDAM Tirta Kampar - Bangkinang City. This research is a survey method. Respondents in this study were employees of PDAM Tirta Kampar - Bangkinang City. The number of samples was 61 employees. There are five variables in this study consisted of four independent variables such as service, productivity, compensation and human resources, and the dependent variable is the performance of PDAM Tirta Kampar - Bangkinang City. According to the research, it can be concluded that the productivity and human resources significantly affect the performance of PDAM Tirta Kampar - City Bangkinang, while service and compensation did not significantly affect the performance of PDAM Tirta Kampar - Bangkinang City. The coefficient of determination shows that the service, productivity, compensation and human resources affect the dependent variable (performance PDAM Tirta Kampar - City Bangkinang) of 50.30%, while the remaining 49.70% influenced by other factors.Keyword : service, productivity, compensation human resource, and the performance